DESIGN OF LONGITUDINAL FLIGHT CONTROL SYSTEM FOR FIGHTER AIRCRAFT USING COEFFICIENT DIAGRAM METHOD - Myrachel, Helga
This research discusses about creating a pitch damper, altitude hold, and speed hold controller using Coefficient Diagram Method (CDM) for aircraft type: General Dynamics F-16 Fighting Falcon. Coefficient Diagram Method is a method that uses the coefficient diagram as a vehicle to carry the characteristics of the controller. With the two main parameters and the shape of the diagram, the information of system’s stability, response, and robustness can be measured qualitatively and quantitatively.